Clinical features of demyelinating optic neuritis with seropositive myelin oligodendrocyte glycoprotein antibody in Chinese patients. Issue 10 (23rd January 2018) - Zhao, Ying; Tan, Shaoying; Chan, Tommy Chung Yan; Xu, Quangang; Zhao, Jie; Teng, Da; Fu, Heyun; Wei, Shihui
Abstract : Background/aims: To investigate the clinical features of Chinese patients with seropositive myelin oligodendrocyte glycoprotein antibody (MOG-Ab) optic neuritis (ON) and patients with seropositive aquaporin-4 antibody (AQP4-Ab) ON. Methods: In this retrospective observational study, sera from patients with demyelinating ON were tested for MOG-Ab and AQP4-Ab with a cell-based assay. Clinical characteristics were compared between MOG-Ab-related ON (MOG-ON) and AQP4-Ab-related ON (AQP4-ON), including visual performances, serum autoantibodies and features on MRI. Results: A total of 109 affected eyes from 65 patients with demyelinating ON (20 MOG-ON and 45 AQP4-ON) were included. The onset age of MOG-ON was younger than AQP4-ON (MOG-ON: 20.2±17.4 years old, AQP4-ON: 35.6±15.7 years old, P=0.001). Onset severity was not different between these two groups (P=0.112), but patients with MOG-ON showed better visual outcomes (P=0.004). Half of the MOG-ON had a relapsing disease course. Nineteen per cent of patients with AQP4-ON presented coexisting autoimmune disorders, but there were no coexisting autoimmune disorders among patients with MOG-ON. Optic nerve head swelling was more prevalent in patients with MOG-ON (P<0.01). Retrobulbar segment involvement of the optic nerve were more common in patients with MOG-ON according to our MRI findings (P<0.01). Patients with MOG-ON showed longitudinally extensive lesion in 30% and chiasm and optic tract involvement in 5%. Conclusions: MOG-ON is not rare in Chinese demyelinating patients. It underwent a severe vision loss at onset but had relatively better visual recovery than patients with AQP4-ON. MOG-ON might have an unique pathogenesis different from AQP4-ON.